Implementation of Rewards and Punishments in Improving the Discipline of Educators and Educational Staff - Utomo, Budi (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
Discipline is an attitude of obedience to the rules that exist in educational institutions. The rules that have been made are often violated. These violations must be a matter of concern to change and foster a culture of discipline. Several factors can be influential in growing and creating a work environment that has a disciplined work culture. This factor can be something that provides a deterrent effect (punishment) or something that provides happiness (reward). Even though discipline and performance are related, this research goes more in-depth into the discipline of educators and education staff. This research aims to determine and analyze the impact of reward and punishment on improving the discipline of educators and education staff in educational institutions. This research is important to carry out as a reference in human resource management in the educational environment. This research method is included in analytical research which consists of two cycles with several stages, namely planning, implementation, observation and reflection. Data collection was carried out by 27 researchers. The location of MIS is very strategic in the middle of Purwodadi urban area, precisely at the Purwodadi intersection. The results of this research illustrate that the application of rewards and punishment can increase the discipline of educators and education staff. This improvement can be seen in the initial conditions, the data shows that the percentage of being late in one month was 78.2%, the percentage of leaving early in one month reached 40.6%, the attendance rate was 93.7%, and the percentage of not being absent was 71 .8%. In cycle 1, the data showed a decrease in tardiness to 75%, leaving early decreased to 28.1%, the attendance rate increased to 96.8%, and the percentage of absences remained 71.8%. Meanwhile in cycle 2, the number of tardiness in one month for 32 teachers and employees was recorded at 68.75%, no one went home early, the attendance rate remained 96.87%, and the percentage of no absences decreased to 58.25%.